Peningkatan Kualitas Belajar Melalui Bimbingan Belajar Di Dusun Ketangi Desa Kampungbaru Kecamatan Tanjunganom - Omami, Ulfina Rizki; Mubtadik, Mohamad Ayyub (STAI Miftahul Ula Nganjuk, 2023)
This article aims to assist the guardians of students in improving learning achievement in the current pandemic period. At this time, education becomes one of the important focuses to note, because online learning has not been able to maximize to improve the quality of education and the level and level of student achievement. Children tend to be lazy to learn if they learn with parents and the results of learning achievement will decrease. It's different from studying in school when studying with a teacher. Therefore, tutoring becomes one of the solutions to help the guardians of students in the learning process of children. This article was written by conducting research and field surveys of children in Ketangi Hamlet and semi-formal interviews with parents. The material from the interview will be analyzed and produce three topics namely social support, personal capacity and participation goals. This article was created by the ABCD method. Tutoring is also useful to motivate student learning and not be left behind even in the current pandemic